Candidate sites and other reference sections for the Global boundary Stratotype Section and Point of the Anthropocene series. (April 2023) - Waters, Colin N; Turner, Simon D; Zalasiewicz, Jan; Head, Martin J
We review and compare proposals for 12 reference sections submitted to the Anthropocene Working Group of the International Subcommission on Quaternary Stratigraphy, of which one will be recommended as the Global boundary Stratotype Section and Point (GSSP) to define the base of the Anthropocene as a series within the Geological Time Scale. The sites span five continents and are located in diverse environments, with all but one sampled by coring. Many sites show annually resolved laminae (here considered optimal for GSSP selection) that can be independently dated radiometrically to confirm a complete succession over the critical interval. An extensive range of proxies, documenting profound human modification of the Earth System at around the mid-20th century interval, has been analysed. Airborne signals (e.g. radioisotopes, fly ash, stable carbon and nitrogen isotopes) provide the most widespread and near-isochronous proxies, applicable across most environments. Additional means of correlation include the appearance of microplastics and persistent organic pollutants, and shifts in heavy metal concentrations and lead isotope ratios. Assemblage changes of microfossils (and some macrofossils) in marine, estuarine and lake settings reflect environmental changes and biological introductions. These systematic and comprehensive datasets, with correlation established between sections, provide the basis for a proposal to formalize the Anthropocene.